Association between serum uric acid level and bone mineral density in men more than 50 years of age - Kim, Sujin; Lee, Seulki; Kwon, Hyuktae (Frontiers in Endocrinology, 2023)
Background: The results of previous studies on the association between serum uric acid levels and bone mineral density and the risk of osteoporosis are controversial. Fat free mass (FFM) is more strongly associated with bone mineral density (BMD) than it is with body fat mass (BFM). Skeletal muscle mass is assumed to contribute indirectly to the relationship between serum uric acid levels and BMD. Therefore, we aimed to evaluate the association between serum uric acid levels and BMD and abnormal BMD (at least osteopenia) by considering body composition in men aged ≥ 50 years. Methods: This was a retrospective observational cross-sectional study. We used data obtained from 2,991 men aged ≥50 years who completed questionnaires, anthropometric surveys, laboratory tests, and bone mineral density scans. A subgroup analysis of 1,135 men who additionally underwent body composition data analysis using Inbody® was performed. Multiple linear regression analysis was used to explore the relationship between serum uric acid levels and Bone mineral density (BMD) at three sites (L1-L4, Femur neck, Femur total). In addition, multiple logistic regression analysis was performed to determine the association of serum uric acid levels with abnormal BMD (at least osteopenia). Results: Positive correlations between serum uric acid levels and BMD at the three sites (L1-L4, Femur neck, Femur total) were observed in unadjusted and fully adjusted models except the BMD of the femoral neck (P-value=0.054). Furthermore, fat free mass (FFM) and skeletal muscle mass index (SMI) showed positive association with serum uric acid level and BMD at three sites, with statistical significance. An increase in serum uric acid level was associated with a lower risk of abnormal BMD after adjusting for confounders including FFM and SMI. Conclusion: Serum uric acid level was positively associated with BMD at three sites and had a protective effect against abnormal BMD after adjusting for multiple confounders, including FFM and SMI, in men aged ≥ 50 years.